Crooklyn - Lee, Spike 1957-; Lee, Joie 1962-; Woodard, Alfre 1952-; Lindo, Delroy 1952-; Jafa, Arthur 1960- (Universal, 1999)
Director Spike Lee fashions a bold, flavorful picture of family life in a crowded but cozy Brooklyn neighborhood nicknamed "Crooklyn" by the Carmichaels, who experience one very special summer in their hometown under difficult but often wonderful circumstances